PENYULUHAN PEMBUATAN SAMURAI (SPRAY ANTI NYAMUK DARI SERAI) DI DESA WONOSARI - Zerfi, Pramesti Wisa; Syakilah, Ahdha; Silalahi , Endah Aulia; Annisha , Chairun; Ardianti, Rini; Jefri; Prastya, Hayyu Andesta; Yahya, Alwi; Yana, Yuda (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Indonesia is a tropical country with relatively high humidity levels, which is a supporting factor for the rapid breeding of mosquitoes. Likewise, Wonosari village, which is located in Rangsang sub-district, Meranti Islands Regency, where the area is surrounded by waterways and plantations, causes mosquitoes to breed quite rapidly. To anticipate the dangers caused by mosquitoes, a SAMURAI (Anti-Mosquito Spray from Lemongrass) socialization activity was carried out by KUKERTA UNRI 2024 students. The aim of this activity was to provide information about the dangers of mosquitoes and training for the Wonosari Village community regarding the use of natural ingredients. those around the home environment such as Lemongrass (Cymbopogon citratus) to repel and prevent mosquito bites. The method used is the lecture method (delivery of material), discussion and training. The series of methods is to provide basic knowledge about the dangers of mosquitoes, followed by providing information and training regarding processing Lemongrass into an anti-mosquito concoction that is environmentally friendly and safe from chemicals. The counseling was held on July 27 2024 in the Wonosari Village Office Hall. The success of the activity was the increase in the basic knowledge of the Wonosari village community regarding the dangers of mosquitoes and how to process the natural ingredient lemongrass into a safe and environmentally friendly anti-mosquito concoction.